Guardiões do Estado e a arregimentação de adolescentes: um estudo a partir do socioeducativo cearense - Krubniki, Thiago (2022)
This dissertation investigated the phenomenon of the regimentation of adolescents by the criminal collective Guardiões do Estado (GDE) from the Unidade de Recepção Luiz Barros Montenegro. The equipment is intended for screening and referrals to centers for compliance with socio-educational measures. This unit was delimited as a field of investigation, located in the city of Fortaleza - CE, Superintendência do Sistema Estadual de Atendimento Socioeducativo do Ceará (SEAS) which operates in the - the place where the researcher worked as a socio-educator from November 2017 to March 2019. As noted there was an intense flow of movements via the internet about the articulations of facções, cyberspace was added to the scope of investigation. This research is of a qualitative nature. The methodology was based on the experience of the dual position of the socio-educator/researcher who had access to a multiplicity of narratives from both adolescents and state agents, field diary reports, ethnographic interviews and analysis of media materials, as well as bibliography in the area of the Sociology of Violence. Axel Honneth's Theory of Intersubjective Social Recognition was mobilized as the main theoretical contribution. As a result, it was found the perception of the impact of the GDE in changing the dynamics of crime in the state scenario by being a precursor in recruiting adolescents. Identity emerged as an element of access to the moral grammar of the GDE - a set of values crystallized in the norms that operationalize the facção - by adolescents admitted to the socio-educational, making it an agglutinating module of identity characteristics of factional youth. It was found that the involvement of adolescents in criminal groups has levels, based on the native categories of the field, namely, envolvido, batizado and simpatizante. Finally, it was found that the various forms of inability of the State to provide decent conditions of existence hurt the practical self-relationships of adolescents, thus contributing to humiliation and offenses to the integrity of these research subjects.